The immunomodulatory effect of inhaled granulocyte-macrophage colony-stimulating factor in cystic fibrosis. A new treatment paradigm - Heslet L; Bay C; Nepper-Christensen S (Dove Medical Press, 2012)
Lars Heslet1, Christiane Bay2, Steen Nepper-Christensen31Serendex ApS, Gentofte, Denmark; 2University of Copenhagen, Medical Faculty, Copenhagen, Denmark; 3Department of Head and Neck Surgery, Otorhinolaryngology, Køge Hospital, DenmarkBackground: Patients with cystic fibrosis (CF) experience recurrent infections and develop chronically infected lungs, which initiates an altered immunological alveolar environment. End-stage pulmonary dysfunction is a result of a long sequence of complex events in CF, progressing to alveolar macrophage dysfunction via a T-helper 2 (TH2) dominated alveolar inflammation with CD20 T-cell activation, induced by the chronic infection and showing a poor prognosis. There is great potential for treatment in transforming the TH2 into the more favorable T-helper 1 (TH1) response.Methods: Current literature in the PubMed database and other sources was reviewed in order to evaluate aspects of the innate alveolar host defense mechanisms and the potential impact on the immunoinflammatory response of inhalation of granulocyte-macrophage colony-stimulating factor (GM-CSF) in patients with CF.Results: It seems that the cellular host defense, (ie, the alveolar macrophage and neutrocyte function) and the inhaled GM-CSF interact in such a way that the so-called tolerant alveolar environment dominated by the TH2 response may be transformed into an active TH1 state with a normal pulmonary host defense. The shift of the TH2 to the TH1 subset dominated by specific and unspecific antibodies may be achieved after the inhalation of GM-CSF. A clinical report has shown promising results with inhalation of GM-CSF in a chronically-infected CF patient treated with several antibacterial and antifungal agents. Inhaled GM-CSF transformed the tolerance toward the Gram-negative infection reflected by the so-called TH2 subset into the more acute TH1 response characterized by recruitment of the T-cells CD8 and CD16, a condition related to better-preserved lung function. This indicated a transformation from a state of passive bacterial tolerance toward the Gram-negative infecting and colonizing bacteria. This GM-CSF effect cannot be achieved by administering the drug via the IV route because the drug is water-soluble and too large to penetrate the alveolocapillary membrane.Conclusions: Inhalation of GM-CSF seems to be a novel way to positively modulate the alveolar environment toward an altered immunological state, reflected by a positive change in the pattern of surrogate markers, related to better preservation of pulmonary function and thus improved outcomes in CF patients. It is suggested that future studies examining standard endpoint variables such as number of infections and amount of antibiotics used should be supplemented by surrogate markers, to reveal any positive cellular and cytokine responses reflecting changes in the alveolar compartment after GM-CSF inhalation. The immunological alveolar environment should be monitored by a specific pattern of surrogate markers. Continued research is clearly indicated and the role of inhaled GM-CSF in modulating pulmonary host defense in CF patients should be investigated in a large study.Keywords: cystic fibrosis, granulocyte-macrophage colony-stimulating factor, TH1 response, TH2 subset, surrogate markers